Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Influence of circumferential gap on the axial compressive behaviour of circular CFDST stub columns: Tests, numerical analysis and design method - Pei-Jia Dai; Rui Wang; Hui Zhao; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Effect of first-stage anode axial position on discharge characteristics of a double-stage anode layer thruster - Rui Ding; Sheng Wen; Zhihao Liu; Jia Liu; Guanrong Hang; Yan Zhang; Ximing Zhu; Yongjie Ding (Advances in Space Research, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Multi-omics analyses identify the modulators COX6A1 and NAL as regulators of silk cocoon formation in Plutella xylostella - Rui-Chang Niu; Qing-Hui Zeng; Wen-Jing Wang; Jia Hu; Tong-Xian Liu; Shi-Ze Zhang (Pesticide Biochemistry and Physiology, 2026)

A novel multi-scale structural equivalent method for jointed rock masses and its application to slope stability analysis - Jia Wang; Wen Zhang; Han Yin; Rui Fu; Qi Sun; Jiali Han; Junqi Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Comprehensive performance of iron-loaded biochar adsorption of U(VI) at an industrial scale based on life cycle assessment and economic analysis - Jia He; Zhou Shen; Yisa Li; Hao Wen; Rui Lu; Shaoli Fan; Jian Gao (Environmental Research, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Process intensification of CO2 desorption by Higee technology: An industrial case study - Han-Zhuo Xu; Rui-Qi Jia; Yong Cai; Liang-Liang Zhang; Fei Gao; Guang-Wen Chu (Chemical Engineering Journal, 2025)

Impact of dietary supplementation with Antheraea pernyi cecropin on growth performance, serum immune indices, intestinal microbial communities and proteomics of Apostichopus japonicus - Zhixin Wen; Rui Mi; Xinghe Chen; Xinyue Jia; Tonghui Ren; Yongxin Sun; Xingfan Du (Animal Feed Science and Technology, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Source analysis of soil selenium and evaluation of soil environmental quality and safety in the eastern area of Zichuan District, Shandong Province - Jia-Wen Cui; Li-Yuan Yang; Jie-Rui Dai; Xi-Qiang Zhao; Jia-Liang Li (Environmental Monitoring and Assessment, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Discovery of the earliest Devonian conodonts from Xinjiang, Northwest China - Jia-Yi Yin; Ladislav Slavík; Jian-Feng Lu; Juan Ma; Yi-Long Liu; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Numerical and laboratory experiments on the toppling behavior of a massive single block: a case study of the Furnas Reservoir, Brazil - Shu-wei Sun; Qiang Wen; Maria do Carmo Reis Cavalcanti; Xiao-rui Yang; Jia-qi Wang (Landslides, 2024)

Analytical calculation method of circular-section rocking steel piers under horizontal cyclic load - Hanqing Zhuge; Jianian Wen; Zhenlei Jia; Qiang Zhang; Qiang Han; Rui Du (Engineering Structures, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Effects of an anti-WSSV transgenic cyanobacterial oral agent on the development, reproduction, and physiology of Daphnia magna - Yupei Tong; Yang Xu; Wen Peng; Dingji Shi; Yuqing Li; Rui Jia (Journal of Applied Phycology, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Numerical Simulation of the Mass Movement Process of the 2018 Sedongpu Glacial Debris Flow by Using the Fluid-Solid Coupling Method - Xing-Yu Long; Yu-Xiang Hu; Bin-Rui Gan; Jia-Wen Zhou (Journal of Earth Science, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Solutions on the periodic background and transition state mechanisms for the higher-order Chen–Lee–Liu equation - Jia-Xue Niu; Rui Guo; Jian-Wen Zhang (Wave Motion, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Selective pollutant degradation with a novel persulfate activation cell resistant to environmental interference - Hui-Shan Meng; Shu-Zhen He; Mei-Mei Wang; Jia-Rui Xi; Jia-Tai Wen; Hong-Wei Luo; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

A bionic mechanical foot with adaptive variable postures travelling on sand - Rui Zhang; Xumin Sun; Dianlei Han; Rui Zhang; Hua Zhang; Jia Ma; Lige Wen; Meng Zou (Journal of Terramechanics, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Oral administration of Synechococcus sp. PCC7942 trans-vp19 and trans-vp (19+28) genes improve the immune and antioxidant capacity in Procambarus clarkii under white spot syndrome virus stress - Jia Yang; Xiao-Ping Chi; Man Li; Wen-hui He; Rui Jia; Pei-Min He (Fish & Shellfish Immunology, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Risk assessment of non-point source pollution based on landscape pattern in the Hanjiang River basin, China - Yi-wen Liu; Jia-ke Li; Jun Xia; Gai-rui Hao; Fang-Yenn Teo (Environmental Science and Pollution Research, 2021)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Analyzing and optimizing yield formation of tomato introgression lines using plant model - Mengzhen Kang; Xiujuan Wang; Rui Qi; Zhi-Qi Jia; Philippe de Reffye; San-Wen Huang (Euphytica, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Limited sampling strategy for the estimation of the area under the concentration-time curve for ganciclovir in Chinese adult renal allograft recipients - Wen-Bin Rui; Hui-Min An; Kun Shao; Xiao-Hui Zhai; Jia-Qian Lu; Shan-Shan Hu; Bing Chen; Pei-Jun Zhou (European Journal of Clinical Pharmacology, 2019)

Microtremor survey and stability analysis of a soil-rock mixture landslide: a case study in Baidian town, China - Wen-wei Gao; Wei Gao; Rui-lin Hu; Pei-fen Xu; Jia-guo Xia (Landslides, 2018)

Composition of stable isotope in precipitation and its influences by different vapor sources in the eastern Qilian Mountains - Wen-xiong Jia; Xing-gang Ma; Xiu-ting Xu; Rui-feng Yuan; Dan Ding; Guo-feng Zhu (Journal of Mountain Science, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Effects of fine particle content and sample scale on the failure properties of loose landslide deposits - Bin-rui Gan; Xing-guo Yang; Ming-liang Chen; Jia-wen Zhou (Arabian Journal of Geosciences, 2018)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Azimuthal cement evaluation with an acoustic phased-arc array transmitter: numerical simulations and field tests - Xiao-Hua Che; Wen-Xiao Qiao; Xiao-Dong Ju; Rui-Jia Wang (Applied Geophysics, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)